Systematic Review on HRV Reference Values - Brozat, Maximillian; Böckelmann, Irina; Sammito, Stefan (Journal of cardiovascular development and disease, 2025)
Heart rate variability (HRV) has been established as a measure for the variation in time intervals between successive cardiac actions as a marker of the autonomic nervous system. However, despite many efforts in this field, there are no reference values that are generally accepted. The objective of this systematic review is, therefore, to present an overview of the studies on HRV normal values published to date, with due consideration of any influencing factors. A systematic database query was carried out in PubMed, Scopus, Ovid Medline, and PsychInfo using the search string “((hrv) or (heart rate variability)) and ((reference values) or (reference range) or (normal values))”. Of the 6640 studies yielded by the query, 58 were used for this systematic review. The STARD-HRV procedure was used to assess the quality of the studies. The studies considered date from 1989 to 2022. The number of subjects examined was between 20 and 84,772. The age of the subjects was between 1 day and 99 years. A total of 51 of the studies examined both male and female subjects. In total, 19 studies used long-term measurements, 22 studies used short-term measurements, and 17 studies used intermediate measuring periods. Many different HRV parameters were analyzed, most often traditional time-domain and frequency-domain ones. Nine studies described the subjects as “healthy” without giving more detailed explanations. There are no generally accepted HRV normal values (yet). Some large studies provide values that may be used for orientation purposes. However, further studies are required to collect HRV normal values. It was not possible to merge the results of the studies in terms of a meta-analysis; this would also not be practical since, among other reasons, the consideration of confounders as well as recording and measuring modalities sometimes vary to a large extent and impede the comparability of the studies. Generally, HRV seems to be influenced by various mechanisms and external factors that are still not fully understood. An exploration of these factors will ultimately allow HRV normal values to be obtained in a manner that is generally accepted.